A comparative study between oral misoprostol and intracervical dinoprostone gel for induction of labour at term in primigravida - Khushboo Satyanarayan Swami; Pundalik Krishna Sonawane (New Indian Journal of OBGYN)
Objectives: To compare the safety and efficacy of oral misoprostol with intracervical dinoprostone gel in terms of progress of labour, maternal and fetal complications when used for induction of labour at term in primigravida. Materials and method: A prospective randomized study from October 2017 to October 2019 was carried out in which 120 primigravida patients with gestational age from 37 to 41 weeks with an indication for induction of labour were randomly divided into 2 groups. In group 1, multiple doses of oral misoprostol (50mcg 4 hourly, maximum up to 6 doses) and in group 2, intracervical dinoprostone gel (0.5mg 6 hourly maximum up to 4 doses) was given for induction of labour. Progress of labour, need for oxytocin augmentation, mode of delivery, maternal and fetal outcome were compared in both groups. Results: Our study showed that in the misoprostol group, 8 (18.2%), 31(43.7%) and 5 (11.4%) patients had induction to delivery time interval of <12 hours, 12-24 hours and >24 hours respectively in comparison with patients in the dinoprostone group where 17(28.3%), 22(36.7%) and 3(5%) patients had induction to delivery time interval of <12, 12 to 24 and >24 hours respectively. The mean induction to delivery interval was significantly higher in the misoprostol group on comparison with the dinoprostone group (18.06 ± 5.64 vs 15.11 ± 6.99 hours) (p - value < 0.05). However, no statistically significant difference was seen concerning to maternal and fetal complications, mode of delivery and need for oxytocin augmentation in between the two groups. Conclusion: Our study showed that intracervical dinoprostone gel shortens the induction to delivery interval significantly when compared with oral misoprostol. However, no statistically significant difference was seen in maternal and fetal complications and the need for oxytocin augmentation in between the groups.